2019
DOI: 10.1016/j.cgh.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors, Gut Microbiota, and Colorectal Cancer Prevention

Abstract: The substantial burden of colorectal cancer and increasing trend in young adults highlight the importance of lifestyle modification as a complement to screening for colorectal cancer prevention. Several dietary and lifestyle factors have been implicated in the development of colorectal cancer, possibly through the intricate metabolic and inflammatory mechanisms. Likewise, as a key metabolic and immune regulator, the gut microbiota has been recognized to play an important role in colorectal tumorigenesis. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
170
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 246 publications
(183 citation statements)
references
References 142 publications
(155 reference statements)
3
170
0
10
Order By: Relevance
“…While some of the heterogeneity may reflect the differences in molecular alterations (e.g., proximal colon cancers are more likely to show MSI, CIMP and BRAF mutation than distal cancers), our observation for a consistently null association between fiber and CRC according to these molecular markers suggests that the subsite findings are unlikely to be explained by these molecular differences across subsites. On the other hand, increasing evidence supports the role of the interplay between fiber and the gut microbiota in CRC development . We recently reported that higher intake of dietary fiber was more strongly associated with lower risk for Fusobacterium nucleatum ‐positive CRC but not Fusobacterium nucleatum ‐negative CRC .…”
Section: Discussionmentioning
confidence: 91%
“…While some of the heterogeneity may reflect the differences in molecular alterations (e.g., proximal colon cancers are more likely to show MSI, CIMP and BRAF mutation than distal cancers), our observation for a consistently null association between fiber and CRC according to these molecular markers suggests that the subsite findings are unlikely to be explained by these molecular differences across subsites. On the other hand, increasing evidence supports the role of the interplay between fiber and the gut microbiota in CRC development . We recently reported that higher intake of dietary fiber was more strongly associated with lower risk for Fusobacterium nucleatum ‐positive CRC but not Fusobacterium nucleatum ‐negative CRC .…”
Section: Discussionmentioning
confidence: 91%
“…This makes meat products an important group of foods which is also consumed globally by a large number of people. But, despite the nutritional value of its components, an excessive consumption of meat, specially processed meat, is related to the risk of cancer development, colon cancer being the most notable . Several processed meat products incorporate soy proteins, due to their beneficial properties for health, and their good nutritional profile, with a large number of essential amino acids .…”
Section: Introductionmentioning
confidence: 99%
“…But, despite the nutritional value of its components, an excessive consumption of meat, specially processed meat, is related to the risk of cancer development, colon cancer being the most notable. 4,5 Several processed meat products incorporate soy proteins, due to their beneficial properties for health, and their good nutritional profile, with a large number of essential amino acids. 6,7 However, soy is a recognized allergen, so it is necessary to look for other vegetable sources of good nutritional quality to replace it.…”
Section: Introductionmentioning
confidence: 99%
“…4), однако материалы о влиянии гипо-и гипертиреоза на канцерогенез толстой кишки отсутствовали, что и стало целью нашего исследования. К тому же колоректальный рак является одной из глобальных проблем всемирного здравоохранения, занимая третье-четвертое место в структуре заболеваемости и второе место по смертности от онкологических заболеваний по всему миру [17].…”
Section: обсуждение полученных результатовunclassified
“…Поиск механизмов и технологий, препятствующих возникновению и/или развитию рака, а также его раннему выявлению, продолжается в различных направлениях [17]. Одним из направлений вторичной профилактики злокачественных новообразованийраннего выявления опухолей или пред опухолевых заболеваний является стратификация факторов риска и формирование групп повышенного риска возникновения опухолей тех или иных топических локализаций [2].…”
Section: Introductionunclassified